Caenorhabditis elegans as a Useful Model for Studying Aging Mutations - Zhang, Siwen; Li, Fei; Zhou, Tong; Wang, Guixia; Li, Zhuo (Frontiers in Endocrinology, 2020)
The Caenorhabditis elegans genome possesses homologs of about two-thirds of all human disease genes. Based on its physiological aging characteristics and superiority, the use of C. elegans as a model system for studies on aging, age-related diseases, mechanisms of longevity, and drug screening has been widely acknowledged in recent decades. Lifespan increasing mutations in C. elegans were found to delay aging by impinging several signaling pathways and related epigenetic modifications, including the insulin/IGF-1 signaling (IIS), AMP-activated protein kinase (AMPK), and mechanistic target of rapamycin (mTOR) pathways. Interestingly, dietary restriction (DR) has been shown to increase the lifespan of numerous metazoans and protect them from multiple age-related pathologies. However, the underlying molecular mechanisms are unclear. In recent decades, C. elegans has been used as a unique model system for high-throughput drug screening. Here, we review C. elegans mutants exhibiting increased in lifespan and age-dependent changes under DR, as well as the utility of C. elegans for drug screening. Thus, we provide evidence for the use of this model organism in research on the prevention of aging.